Upaya meningkatkan motivasi dan hasil belajar matematik siswa melalui model pembelajaran project-based learning - Nur Hasanah; Marzuki Marzuki; Irfan Rusmar; Hamdani Hamdani (Mahesa Research Center, 2023)
In the era of globalization education is very important, because education can create human beings who are of high quality, character, and have broad insights. The purpose of this study was to find out that the use of project-based learning models can increase motivation and student learning outcomes in fraction material in class V of Elementary School (SD). This research is classroom action research conducted through 2 cycles using the spiral model by C. Kemmis and MC. Taggart. The subjects in this study were fifth grade elementary school students with a total of 24 students. The data collection technique uses a comparative descriptive method by comparing the results before the action is given, namely, the pre-cycle until the action is completed. In the pre-cycle stage, the percentage of students' learning motivation was obtained by 29.1% in the medium category, 70.8% in the low category and for the high category at this pre-cycle stage, 0%. Then gradually in cycle 1 it increased to 33.3% in the high category, 45.8% in the medium, and 20.8% in the low category. Finally, in cycle 2, there was a significant increase in the high category, namely 83.3%, medium 12.5%, and 4.1% low category. The increase in students' learning motivation also affected their learning outcomes, where in the pre-cycle the percentage was 41.6%, and it experienced a gradual increase in cycle 1 with a percentage of 66.6%. Phase 2 cycle also increased with a percentage of 83.3%. In conclusion, using the project-based learning model can support student learning activities in increasing motivation, and students' mathematical learning outcomes in the subject of fractions in elementary school.